2011
DOI: 10.1203/pdr.0b013e3182092a9a
|View full text |Cite
|
Sign up to set email alerts
|

Paneth Cell Hyperplasia and Metaplasia in Necrotizing Enterocolitis

Abstract: Paneth cell dysfunction has been suggested in necrotizing enterocolitis (NEC). The aim of this study was to i) study Paneth cell presence, protein expression, and developmental changes in preterm infants with NEC and ii) determine Paneth cell products and antimicrobial capacity in ileostomy outflow fluid. Intestinal tissue from NEC patients (n = 55), preterm control infants (n = 22), and term controls (n = 7) was obtained during surgical resection and at stoma closure after recovery. Paneth cell abundance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…However, to the best of our knowledge, an expansion of the Paneth cell population has not been previously documented for ST or other enteric bacterial infections. Only very recently, Paneth cell hyperplasia has been associated with necrotizing enterocolitis in premature infants (48). We found that an activation of the Wnt signaling pathway accompanied the expansion of the Paneth cell population in ST-infected mice.…”
Section: Discussionmentioning
confidence: 64%
“…However, to the best of our knowledge, an expansion of the Paneth cell population has not been previously documented for ST or other enteric bacterial infections. Only very recently, Paneth cell hyperplasia has been associated with necrotizing enterocolitis in premature infants (48). We found that an activation of the Wnt signaling pathway accompanied the expansion of the Paneth cell population in ST-infected mice.…”
Section: Discussionmentioning
confidence: 64%
“…The present study suggests that HD5 expression coincides with PC development until a GA of 28 wk; in the period starting from 29 wk of GA, HD5 expression increases more rapidly than the number of PCs. PCs with their defensin expression, such as HD5, play a key role in the intestinal innate immunity and development of diseases (13)(14)(15). PCs with their defensin expression are previously described in the pathophysiology of Crohn's disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…34,35 The barrier function of the preterm gastrointestinal tract is immature, both in its structure and secretory activity. [36][37][38][39][40] Mucosal permeability of the preterm gut is higher compared …”
Section: Risk Factors Associated With Nec Prematurity and Low Birth Wmentioning
confidence: 99%
“…37 In preterm infants affected by NEC, mucosal injury has been shown to lead to increased nitric oxide production which, in turn, accentuates epithelial injury, thus increasing the susceptibility to NEC. 38 The preterm gut affected by NEC has also been shown to have fewer and immature Paneth cells 15,39 (specialized crypt cells in the human intestine producing natural antimicrobials, such as lysozyme) with near absence of lysozyme. 40 The immature nature of the preterm immune system is thought to play a major role in the development of NEC.…”
mentioning
confidence: 99%